2018
DOI: 10.1007/s00424-018-2124-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of G protein-regulated inducer of neurite outgrowth 3 (GRIN3) in β-arrestin 2-Akt signaling and dopaminergic behaviors

Abstract: The G protein-regulated inducer of neurite growth (GRIN) family has three isoforms (GRIN1-3), which bind to the Gαi/o subfamily of G protein that mediate signal processing via G protein-coupled receptors (GPCRs). Here, we show that GRIN3 is involved in regulation of dopamine-dependent behaviors and is essential for activation of the dopamine receptors (DAR)-β-arrestin signaling cascade. Analysis of functional regions of GRIN3 showed that a di-cysteine motif (Cys751/752) is required for plasma membrane localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…GPRIN3 was upregulated in GC cell lines and was negatively modulated by miR-6838-5p in GC. GRIN3 is also reported to be upregulated in striatum and interact with β-arrestin 2 [35]. Besides, rescue assays in our study demonstrated that GPRIN3 overexpression counteracted the inhibition from miR-6838-5p upregulation in the proliferative, migratory, and invasive capabilities of GC cells.…”
Section: Discussionsupporting
confidence: 55%
“…GPRIN3 was upregulated in GC cell lines and was negatively modulated by miR-6838-5p in GC. GRIN3 is also reported to be upregulated in striatum and interact with β-arrestin 2 [35]. Besides, rescue assays in our study demonstrated that GPRIN3 overexpression counteracted the inhibition from miR-6838-5p upregulation in the proliferative, migratory, and invasive capabilities of GC cells.…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, the decrease in excitability promoted by quinpirole (a D 2 R agonist) described previously (Cazorla et al, 2012;Lalchandani et al, 2013) was blunted in D 2 -eGFP/GPRIN3 KO cells and reversed by the viral inactivation of GPRIN3 (with pSicoR shGPRIN3), indicating profound changes in D 2 R function, which are in line with the purported role of the GPRIN family in mediating the G␣i/o signaling. However, on all the results discussed above, it cannot be ruled out the possibility that our observations are caused by the loss of control over the D 2 R desensitization by inactivating GPRIN3 as previously described (Mototani et al, 2018).…”
Section: Discussionmentioning
confidence: 61%
“…GPRIN3, on the other hand, has a much less defined role but is highly expressed in the brain and has recently been tagged as a partner of ␤-arrestin-2, regulating dopamine receptor desensitization with impact on selective behavioral tasks (Mototani et al, 2018). Here, we show the preferential expression of the GPRIN3 in iMSNs, and its presence in much higher levels in the striatum compared with the PFC, hippocampus, or cerebellum.…”
Section: Introductionmentioning
confidence: 71%
“…Western blotting was conducted with commercially available antibodies [21,28,30,31]. Primary antibodies directed against the following proteins were purchased from the indicated sources: Akt (1:1000, #9272) [26], phospho-Akt (1:1000, Ser-473, #9721) [26], CaMKII (1:1000, #3362) [32], phospho-CaMKII (1:1000, Thr-286, #3361) [32], BAX (1:1000, #2772) [21], LC3 (1:1000, #12741) [21], Bcl-2 (1:1000, #3498) [28], phospho-mTOR (1:1000, Ser-2448, #5536; Ser-2481, #2974) [26], mTOR (1:1000, #2972) [26] and RIP3 (1:1000, #95702) [33] from Cell Signaling Technology (Boston, MA, USA), p62 (#PM045) from MBL (Nagoya, Japan), and GAPDH (sc-25778) [26] from Santa Cruz Biotechnology (Santa Cruz, CA, USA), phosphorylated phospholamban (PLN) (1:5000, phospho-Ser-16, #A010-12; 1:1000, phospho-Thr-17, #A010-13) [21] and PLN (1:2000, #A010-14) [21] from Badrilla (Leeds, UK).…”
Section: Plos Onementioning
confidence: 99%